Bilateral absence of the kidneys and ureters. Three cases reported in one family. - Pashayan, H M (1977)
Three infant boys with bilateral absence of the kidneys and hypoplasia of the lungs are described. Two of the infants were brothers and the third was a first cousin. They were born to 2 sisters whose husbancs were unrelated to their wives and to each other. None of the parents had renal problems. The occurrence of this syndrome in 2 male sibs is suggestive of an autosomal recessive inheritance pattern which has been previously described. An additional male first cousin born to the mother's sister is sugesstive of sex-linked inheritance for this particular family, an inheritance pattern not previously described.